HEDONISME DALAM LIRIK LAGU DANGDUT - Ahmad Wahani Adid (Universitas Wijaya Kusuma Surabaya, 2019)
Dangdut song is one of type art as literature, it is a human cultural activities. Based on this background, the focus in this study is: (1) the culture of sexuality, (2) the culture of materialism, (3) the culture of consumerism in the lyrics of dangdut songs. It used theory in this research is cultural studies the studies based on an interdisciplinary perspective that some theories are intertwined the culture of hedonism. The research used the descriptive qualitative research method. Based on the results of research, we can conclude (1) the culture of sexuality that are found in the lyrics of dangdut songs. It is related with the genitals, body and sexual exploitation againts women, sexual relations outside marriage and sex as infidelity, (2) the culture of materialism, it is assumes if everything is just based properties or goods that look, also reflected in the dangdut song that leads into hedonism, and (3) in the lyrics of dangdut songs also there is a culture of consumerism and wasteful consume excessive behavior. In addition, there is also a culture of consumerism in the form of things that are not allowed according to the religious such as liqour.